PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN BIPA BAGI PENUTUR ASING TINGKAT PEMULA - Ramadani Khusnul Khotimah; Resdianto Raharjo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the utilization of digital media in teaching Indonesian for Foreign Speakers (BIPA) at the beginner level. The purpose of this research is to describe the implementation of digital media in BIPA learning and identify its advantages and challenges in the learning process. This study employed a descriptive qualitative method involving BIPA teachers and beginner-level foreign learners as research participants. Data were collected through observation, interviews, and documentation. The findings revealed that digital media, such as learning videos, presentation slides, online meeting platforms, and interactive applications, played an important role in improving students’ motivation, engagement, and understanding of Indonesian language materials. The use of digital media also created a more interactive and flexible learning environment for both teachers and learners. However, several challenges were identified, including unstable internet connections and differences in learners’ digital literacy. Overall, the utilization of digital media contributed positively to the effectiveness of beginner-level BIPA learning and supported the development of innovative language teaching strategies in the digital era.